Clinical Patterns, Survival, Comorbidities, and Treatment Regimens in 149 Patients With Pemphigus in Tuscany (Italy): A 12-Year Hospital-Based Study - Quintarelli, Lavinia; Coi, Alessio; Maglie, Roberto; Corrà, Alberto; Mariotti, Elena Biancamaria; Aimo, Cristina; Ruffo di Calabria, Valentina; Verdelli, Alice; Bianchi, Beatrice; Del Bianco, Elena; Antiga, Emiliano; Caproni, Marzia (Frontiers in Immunology, 2022)
Introduction Pemphigus encompasses a group of muco-cutaneous autoimmune bullous diseases characterized by the loss of adhesion between keratinocytes. The disease is associated with increased morbidity and mortality. Materials and Methods We characterized clinical patterns, survival, comorbidities and drug prescriptions in pemphigus patients referred to the Dermatology service of the University of Florence from January 2010 to December 2021. Results A total of 149 patients were identified (F/M Sex Ratio = 2.0). Median age at diagnosis was 57.7±17.2years; 108 patients were diagnosed with pemphigus vulgaris (PV) (72.5%) and 35 (23.5%) with pemphigus foliaceus (PF). Paraneoplastic pemphigus (PNP) and IgA-pemphigus accounted for 3 patients each. The overall survival was 86.9%. Accordingly, fourteen (9%) patients died during the study period. The average age at death was 77.8±9.3. Age at diagnosis was a risk factor for death in pemphigus patients. Average concentration of Dsg3-IgG and Dsg1-IgG was 85.6±68.8 and 75.9±68.4, respectively. The most serious comorbid diseases included cerebro- and cardiovascular accidents and malignancies. Regarding the treatment regimen, we found a substantially stable use of systemic steroids in the 2010-218 period; the prevalence of use of mycophenolic acid increased, while that of azathioprine decreased. The use of rituximab showed the highest increase in the 2013-2018 period. Proton-pump inhibitors and antibiotics were the most frequently prescribed non-immunomodulating drugs. Conclusions In this large series of the patients, pemphigus patients showed a high incidence of serious comorbid diseases, highlighting the importance of a multidisciplinary approach for a proper management of the patients. Rituximab was the immunomodulating drug showing the highest increase in use over time, reflecting the growing evidence of its efficacy as a first-line treatment in pemphigus.